When visual metacognition fails: widespread anosognosia for visual deficits - Michel, M; Gao, Y; Mazor, M; Kletenik, I; Rahnev, D (Cell Press, 2024)
Anosognosia for visual deficits - cases where significant visual deficits go unnoticed - challenges the view that our own conscious experiences are what we know best. We review these widespread and striking failures of awareness. Anosognosia can occur with total blindness, visual abnormalities induced by brain lesions, and eye diseases. We show that anosognosia for visual deficits is surprisingly widespread. Building on previous accounts, we introduce a framework showing how apparently disparate forms of anosognosia fit together. The central idea is that, to notice a deficit, individuals need to form expectations about normal vision, compare expectations and visual input, and judge any mismatch at the metacognitive level. A failure in any of these three steps may lead to unawareness of visual deficits.